Technique for Selecting Superior Seeds in Red Chili Plants (Capsicum annuum L.) Using Salt Solution (Naci) and Red Onion Solution (Allium Ascanonicum L) - Waruwu, Destini Friska Bestari; Lombu, Sri Oktafiyanti; Lombu, Sri Oktafiyanti; Waruwu, Windy Syahputri Mawar; Waruwu, Lince Febryani; Halawa, Febe Juniati Halawa; Telaumbanua, Miskaria Murni; Farasi, Wirandi Ahmad Ridho; Lase, Natalia Kristiani (Jurnal Agroekoteknologi Terapan, 2025)
The technique for selecting red chili seeds (Capsicum annuum L.) is one way to determine the level of excellence of superior seeds and which are suitable for use as seeds for new plants. This research aims to assess seed selection techniques using a solution of shallots (Allium Ascanonicum L) and salt (NaCl) on red chili plant seeds. This research was carried out in the Faculty of Science and Technology, Nias University laboratory in September 2024. The research method used in this research was an experimental research method using red chili seeds (Capsicum annuum L.) as the main research ingredient in a salt solution and shallots. The research results, namely knowing the seed selection technique using a solution of shallots and salt, will help determine the level of superiority of good seeds to be used as superior seeds and can improve the quality of good products. The onion and salt solution significantly affects the process of soaking the seeds. Keywords: Selection of red chili seeds (Capsicum annuum L.), shallot solution, salt solution. Abstrak Teknik pemilihan benih cabe merah (Capsicum annuum L.) adalah salah satu cara untuk mengetahui tingkat keunggulan benih yang unggul dan yang layak dijadikan benih tanaman baru. Penelitian ini bertujuan untuk mengetahui teknik pemilihan benih dengan menggunakan larutan bawang merah (Allium Ascanonicum L) dan garam (NaCl) pada benih tanaman cabe merah. Penelitian ini dilaksanakan di laboratorium Fakultas Sains dan Teknologi Universitas Nias pada bulan September 2024. Metode penelitian yang digunakan dalam penelitian ini yaitu metode penelitian eksperimen dengan menggunakan benih cabe merah sebagai bahan utama penelitian pada larutan garam dan bawang merah. Hasil penelitian yang dilakukan yaitu teknik pemilihan benih dengan menggunakan larutan bawang merah dan garam, membantu mengetahui tingkat keunggulan benih yang baik untuk dijadikan benih unggul dan dapat meningkatkan kualitas produk yang baik. Larutan bawang merah dan garam memiliki pengaruh yang nyata dalam proses perendama benih tersebut. Kata Kunci: Pemilihan benih cabe merah (Capsicum annuum L.), larutan bawang merah, larutan garam.